Præskription og deskription i nyere færøsk leksikografi - Thomsen, Johnny (LexicoNordica, 2002)
The present paper deals with the particular Faroese problem of a significant lexical difference between the codified written language and oral language based upon writing on the one hand and neutral speech on the other. The difference between these two types of Faroese is described. With examples from four dictionaries published in the period 1992 to 1998 it is being demonstrated how Faroese purist lexicography describes the language by excluding frequent words, including neologisms etc. Further, the problems of permanent Faroese-Danish language contact are described briefly and the special lexicographical problems arising form the constant interaction between Danish and Faroese are being touched upon. The consequences of the purist lexicographical approach are briefly dealt with.